An integrated flow cytometry analysis of 286 mature B cell neoplasms identifies CD13 as a useful marker for diagnostic subtyping. (31st July 2018) - Lau, Hubert; Nagy, Alexandra; Atwater, Susan K.; Cascio, Michael J.; Ohgami, Robert S.
Abstract: Introduction: CD13 is a myeloid associated antigen, which may be expressed by a subset of B cell lymphomas; however, the significance of its expression along with other B cell associated antigens is not well characterized. Methods: Two hundred and eighty‐six mature B cell neoplasms with flow cytometric analysis performed at the time of diagnosis were identified. Expression of CD13, CD45, CD19, CD20, CD5, CD10, CD38, CD22, CD23, FMC7, and kappa and lambda light chains was assessed for each case and correlated with clinicopathologic features. Results: CD13 expression was associated specifically with cases of lymphoplasmacytic lymphoma (LPL) (16/26)‐ and FMC7‐positive chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) (11/30). No cases of follicular lymphoma (FL) expressed CD13 (0/48). Across all B cell neoplasms, CD13 expression positively correlated with FMC7 co‐expression and kappa light chain restriction and negatively correlated with CD10 co‐expression and lambda light chain restriction. No significant association of CD13 with overall or disease free survival in B cell neoplasms was seen. Conclusion: CD13 expression is present more often in LPL‐ and FMC7‐positive CLL/SLL than other mature B cell lymphoma subtypes and absent in cases of FL and may be a useful feature for diagnostic subtyping.